2014
DOI: 10.1152/jn.00077.2014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal response properties of koniocellular (blue-on and blue-off) cells in marmoset lateral geniculate nucleus

Abstract: Visual perception requires integrating signals arriving at different times from parallel visual streams. For example, signals carried on the phasic-magnocellular (MC) pathway reach the cerebral cortex pathways some tens of milliseconds before signals traveling on the tonic-parvocellular (PC) pathway. Visual latencies of cells in the koniocellular (KC) pathway have not been specifically studied in simian primates. Here we compared MC and PC cells to "blue-on" (BON) and "blue-off" (BOF) KC cells; these cells car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 93 publications
4
18
0
Order By: Relevance
“…We included units where two consecutive bins in the PSTH exceeded the spontaneous rate by at least 2.5 SD of that rate and performed a linear regression from the first of those bins to the bin that contained the response peak. Latency was defined as the intersection of the regression line and the spontaneous rate (Pietersen et al 2014). All fits were inspected manually: where the automated procedure clearly failed, a line was fit to the rising phase of the PSTH using manually selected data points and the latency obtained as above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included units where two consecutive bins in the PSTH exceeded the spontaneous rate by at least 2.5 SD of that rate and performed a linear regression from the first of those bins to the bin that contained the response peak. Latency was defined as the intersection of the regression line and the spontaneous rate (Pietersen et al 2014). All fits were inspected manually: where the automated procedure clearly failed, a line was fit to the rising phase of the PSTH using manually selected data points and the latency obtained as above.…”
Section: Discussionmentioning
confidence: 99%
“…Latency was defined as the intersection of the regression line and the spontaneous rate (Pietersen et al . ). All fits were inspected manually: where the automated procedure clearly failed, a line was fit to the rising phase of the PSTH using manually selected data points and the latency obtained as above.…”
Section: Methodsmentioning
confidence: 97%
“…At first sight the data in Fig. A and C seem to contradict the literature on identified X‐ and Y‐cells (Frishman et al ., ; Weng et al ., ) or primate parvocellular and magnocellular neurones (Pietersen et al ., ). There are, however, indications that this relationship is not ubiquitous.…”
Section: Resultsmentioning
confidence: 97%
“…Pietersen et al . () found that the visual latencies of blue‐ON cells in marmoset LGN are 10–20 ms longer than those of parvocellular or magnocellular cells, however, another study from macaques (Tailby et al ., ) reported only trivial differences between blue‐ON and parvocellular cells. Our results are broadly consistent with these results: we found visual latencies of blue‐ON cells from the cat LGN lag behind those of achromatic cells by around 7–13 ms and the difference is on the margin of statistical significance (Figs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation